MULTI-RAT BASED ADAPTIVE QUALITY OF SERVICE (QOS) MANAGEMENT IN WBAN - Irshad, Tayyaba; Shan, Rafi-us; Ahmad, Raja Wasim; Khalid, Abbas; Ab Hamid, Siti Hafizah (Malaysian Journal of Computer Science, 2020)
Wireless body area network (WBAN), a sub-branch of wireless sensor networks (WSN), helps continuous monitoring of various conditions and states of a human body. It has vast application areas, including self-care, battlefield, health, sports, assisted living, and entertainment. In WBAN, sensors (e.g., ECG, EEG, EMG, and temperature) may transmit sensed information of the subject under observation to a personal server which directs it to the main server for the analysis. The requirement of an application in terms of reliability and delay varies depending on the situation and environment. For instance, the high network delay and jitter for a health application may lead to a human death due to urgent response requirement. The major challenge faced by WBAN is to offer high Quality of Service (QoS). To ensure high QoS in WBAN, different techniques are proposed but all these techniques have considered different layers for different radio technologies. The current study put forwards an adaptive Multi-Radio Access Technologies (multi-RAT) based platform for the WBAN. Multi-RAT proposes a convergence/adaptation layer to entertain increasing request rate of WBAN applications. As a result, throughput, delay, and blocking probability for each request are minimized.